Estimating pure tone behavioural thresholds with the dichotic multiple frequency auditory steady state response compared to an auditory brainstem reponse protocol in normal hearing adults - Hugo, Rene (University of Pretoria, 2013)
Dissertation (MA (Communication Pathology))--University of Pretoria, 2001.